Recovery after curettage of grapevines with esca leaf symptoms - LECOMTE, Pascal; CHOLET, Céline; BRUEZ, Emilie; MARTIGNON, Tommaso; GIUDICI, Massimo; SIMONIT, Marco; ALONSO UGAGLIA, Adeline; FORGET, Dominique; MIRAMON, Jérôme; ARROYO, Matthieu; et al. (Phytopathologia Mediterranea, 2022)
Grapevine curettage was re-introduced in France in the early 2000s, and is important for facilitating recovery of plants from esca disease. This surgical practice involves removal of deadwood of vines with leaf symptoms, focusing on white rot generally observed at the centres of grapevine trunks. Assessment of the efficacy of this practice was initiated in the Bordeaux region in 2014. One ‘Sauvignon Blanc’ vineyard severely affected by esca was initially surveyed in the summer of 2014, to identify and treat vines with esca foliar symptoms. Annually thereafter, from 2014 to 2018, selected vine stocks were curetted. Two other ‘Sauvignon Blanc’ vineyards also displaying high levels of esca damage were added to the study in 2015 and 2016. Curettage treatments ceased in 2018, resulting in 11 trials (vineyard × year combinations). In total, 856 vines (422 curetted and 434 control vines) were then surveyed annually up to 2021, for assessments and comparisons of esca development. At each site, plants with esca symptoms recovered well after curettage: on average 85% of all curetted vines became asymptomatic the year immediately after the treatment. Six years after treatment, for curettage campaigns carried out in 2014 and 2015, more than half of the curetted vines were symptom-free, whereas <12% of the control vines were asymptomatic, and gradual loss of efficacy was observed at each site. The mean annual proportion of efficacy erosion was approx. 8% per year. This study highlights the possible short- and mid-term benefits of trunk surgery to enable recovery of esca-affected vines, and for them to recover and remain leaf-asymptomatic for several years.